(untitled) (Journal of Geography and Environmental Management, 2017)
During the warm period of year the physics – statistical forecasting models of this size allows to develop identification of synchronous and asynchronous correlative communications of seasonal rainfall with various characteristics of circulation of the atmosphere.The main goal of the study is to evaluate and compare the synchronous and asynchronous statistical relationships of mean seasonal precipitation in Eastern Kazakhstan with the baric fields at the grid nodes of the Northern Hemisphere and the circulation characteristics. Such characteristics were taken: the index of the North Atlantic Oscillation and the number of days with circulation types according to M.Kh. Baidal, which can be used in physical and statistical forecast models. Physical and statistical forecast models of different weather characteristics are often created on the basis of linear multiple regression equations that contain a certain set of predictors. The physical aspect of selecting predictors for the multiple regression equation in precipitation prediction problems is quite diverse. Such relationships are often established by calculating the correlation coefficients between the predicted value and the predictors included in the regression equation that have a significant correlation relationship. In the study, the correlation of averaged over the territory of seasonal precipitation in the east of Kazakhstan with different circulation characteristics was evaluated. The average averaged seasonal precipitation amounts averaged over the territory of East Kazakhstan according to the classes «less than the norm», «norm» and «above the norm» were done, the frequency of each class was determined and a catalog of years with an excess of seasonal precipitation exceeding 1.2 Sx was compiled.